2017
DOI: 10.1103/physrevlett.119.246401
|View full text |Cite
|
Sign up to set email alerts
|

Reflection-Symmetric Second-Order Topological Insulators and Superconductors

Abstract: Second-order topological insulators are crystalline insulators with a gapped bulk and gapped crystalline boundaries, but topologically protected gapless states at the intersection of two boundaries. Without further spatial symmetries, five of the ten Altland-Zirnbauer symmetry classes allow for the existence of such second-order topological insulators in two and three dimensions. We show that reflection symmetry can be employed to systematically generate examples of second-order topological insulators and supe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
715
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 959 publications
(745 citation statements)
references
References 51 publications
(132 reference statements)
6
715
0
1
Order By: Relevance
“…The experimental discovery of materials known as higher-order topological insulators corroborates theoretical predictions and expands the toolbox for examples [7][8][9] , such that ordinary topological insulators appear at the first order. A higher order insulator can be thought of as having a nested topological structure.…”
Section: Waves Corneredsupporting
confidence: 63%
“…The experimental discovery of materials known as higher-order topological insulators corroborates theoretical predictions and expands the toolbox for examples [7][8][9] , such that ordinary topological insulators appear at the first order. A higher order insulator can be thought of as having a nested topological structure.…”
Section: Waves Corneredsupporting
confidence: 63%
“…The quest for topological 0D cavity modes in 2D electromagnetic‐wave systems, which could serve as an important ingredient to build‐up of robust electromagnetic‐wave/photonic devices, was unsuccessful until very recently . Such an achievement was realized using the higher‐order topological insulators . Unlike the conventional D ‐dimensional topological insulators which have ( D −1)‐dimensional topological gapless boundary states, a D ‐dimensional higher‐order topological insulator gives rise to ( D − 2)‐dimensional (or even lower‐dimensional) topological gappless boundary states, in addition to the ( D − 1)‐dimensional gapped boundary states, offering a paradigm beyond the conventional bulk‐boundary correspondence.…”
mentioning
confidence: 99%
“…[28,35] Such an achievement was realized using the higher-order topological insulators. [27][28][29][30][31][32][33][34][35][36][37] Unlike the conventional D-dimensional topological insulators which have (D−1)-dimensional topological gapless boundary states, a D-dimensional higher-order topological insulator gives rise to (D − 2)-dimensional (or even lower-dimensional) topological gappless boundary states, in addition to the (D − 1)-dimensional gapped boundary states, offering a paradigm beyond the conventional bulk-boundary correspondence. Through the concept of higher-order topological insulators, it has been demonstrated that topological 0D corner states can emerge in mechanical metamaterials, [27] microwave circuits with lumped components, [28] and coupled optical waveguides.…”
mentioning
confidence: 99%
“…Also, the above reported acoustic implementations have, for the most part, been implemented inside waveguides or were designed in an acoustically rigid enclosure, which hinders their capabilities from external insonification. [23][24][25][26] Most recently, the concept of higher-order TIs (HOTIs), [27][28][29][30][31][32][33] which is a special class of TIs with unconventional bulk-boundary correspondence, was proposed to support the existence of the lower-dimensional boundary states. The advantage in using holey metamaterials resides in their high levels of integration and miniaturization at scales much smaller than the sound wavelength.…”
mentioning
confidence: 99%
“…Concerning this matter, the findings will thus have the capability to push forward exciting applications for robust acoustic imaging way beyond the diffraction limit.The discovery of topological insulators (TIs) [1,2] and the strikingly robust transmission of reflectionless edge states have boosted intense research in classical systems such as photonics, [3][4][5][6][7][8][9] acoustics, [10][11][12][13][14][15][16][17][18][19][20][21][22] and mechanics. [23][24][25][26] Most recently, the concept of higher-order TIs (HOTIs), [27][28][29][30][31][32][33] which is a special class of TIs with unconventional bulk-boundary correspondence, was proposed to support the existence of the lower-dimensional boundary states. For example, in d-dimensional (dD) systems, a second-order TI (SOTI) has dD gapped bulk states, (d − 1)D gapped boundary states, and (d − 2)D gapless boundary states, which are 0D corner states…”
mentioning
confidence: 99%